Recent, slow normal and strike‐slip faulting in the Pasto Ventura region of the southern Puna Plateau, NW Argentina. Issue 1 (28th January 2013) - Zhou, Renjie; Schoenbohm, Lindsay M.; Cosca, Michael
<x xml:space="preserve">Abstract</x> [1] Recent normal and strike‐slip faulting on the Puna Plateau of NW Argentina has been linked to lithospheric foundering, gravitational spreading, plate boundary forces and a decrease in crustal shortening from north to south. However, the timing, kinematics and rate of extension remain poorly constrained. We focus on the Pasto Ventura region (NW Argentina) located on the southern Puna Plateau and recent deformation (<1 Ma). Field mapping and kinematic analysis across offset volcanic cinder cones show that the overall extension direction is subhorizontal, is oriented NE‐SW to NNE‐SSW, and occurs at a slow, time‐integrated rate of 0.02 to 0.08 mm/yr since at least 0.8–0.5 Ma. A regional compilation from this study and existing data shows that recent extension across the Puna Plateau is subhorizontal but varies in azimuthal orientation dramatically. Data from the Pasto Ventura region are consistent with a number of models to explain normal and strike‐slip faulting on the Puna Plateau, all of which likely influence the region. Some role for lower lithospheric foundering through dripping appears to be seen based on the regional extension directions and ages of mafic volcanism in the southern Puna Plateau.